1967
DOI: 10.1172/jci105549
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Pulmonary Ventilation and Perfusion in Obesity *

Abstract: Summary. Five women and three men, all obese and weighing 95 to 140 kg, were studied by routine pulmonary function tests and by a radioactive xenon technique, while seated upright at rest, to measure the regional ventilation and perfusion distribution in the lung.In four subjects in whom the expiratory reserve volume averaged 49% of predicted normal, the ventilation distribution as measured with 133xenon was normal. In the remaining four subjects, in whom the expiratory reserve volume was reduced to less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
7

Year Published

1967
1967
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(120 citation statements)
references
References 10 publications
8
105
0
7
Order By: Relevance
“…A reduced lung function of variable degree was found in subjects with severe obesity and OHS. 3,17 In aggreement with our data, Sahebjiami and Gartside 7 demonstrated that obese subjects with hypercapnia, in the absence of any other disease process and with normal FEV 1 /FVC, were characterized by higher BMI and worse respiratory function. However, not only body weight, but also the fat distribution has been found to play a pivotal role in determining the reduction of FVC in obese subjects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A reduced lung function of variable degree was found in subjects with severe obesity and OHS. 3,17 In aggreement with our data, Sahebjiami and Gartside 7 demonstrated that obese subjects with hypercapnia, in the absence of any other disease process and with normal FEV 1 /FVC, were characterized by higher BMI and worse respiratory function. However, not only body weight, but also the fat distribution has been found to play a pivotal role in determining the reduction of FVC in obese subjects.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, ventilation can be reduced at lung bases, mainly in patients with reduced ERV, leading to arterial hypoxaemia. 3 Several studies on diurnal hypoventilation in patients affected by obesity hypoventilation syndrome (OHS) have been performed, [4][5][6] whereas few data exist on diurnal PaCO 2 tension in apparently healthy nonsmoking obese patients. 7 It is noteworthy that several studies demonstrated a wide array of respiratory disturbances during sleep (hypoventilation, obstructive apnoea-hypopnoea events, and 'flow limitation') in obese individuals, 8,9 but no information is available about the possible relationship between diurnal PaCO 2 tension and sleep-respiratory disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of obesity, especially in those cases presenting abdominal fat deposition, ventilation of the base of the lungs is reduced, especially in those individuals presenting lower ERV values (32) . Various studies have shown altered pulmonary function in individuals with class III obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Closure in nonasthmatics was predominantly in the lung bases, whereas in asthmatic subjects the distribution of closure was patchy, with peripheral wedge-shaped defects in both apical and basal lung regions [5]. Basal ventilation appears to be impaired in obese subjects [29], suggesting that closure may be confined to the basal lung zones i.e. topographically similar to that in nonasthmatics [5].…”
Section: Discussionmentioning
confidence: 99%